Managing Iris Cysts with Surgical Excision: A Case Series: Poster Presentation - Case Series - Ophthalmologist - Dini Dharmawidiarini; Farida Moenir; Sitorus, Tigor Santoso; Afifah, Azzahra; Napitupulu, Sanata PH (Majalah Oftalmologi Indonesia, 2023)
Introduction : Iris cysts are uncommon iris tumors. Primary iris cysts are congenital and usually not detected until late into the first or second decade of life. Secondary iris cysts have history of trauma or intraocular surgery. Small and asymptomatic iris cysts should be monitored, whereas larger cysts require treatment as they cause complications. Case Illustration : Case 1 a 17-year-old teenager had blurred vision without prior intraocular trauma or surgery. Anterior segment examination of the left eye revealed an oval, light brown, and semi-translucent cyst. Case 2 a 15-year-old girl had blurred vision and enlarging white spot in right eye with history of penetrating ocular trauma. Patient had undergone immediate penetrating repair followed by combination of pupilloplasty and cataract surgery. Anterior segment examination of the right eye showed corneal scar and cystic lesion. Both cysts extended to corneal endothelium and were managed surgically. Discussion : Larger cysts, especially with complications, require cyst aspiration, laser therapy, injections of antiproliferative agents, or surgery. We decided to surgically aspirate and excised iris walls to remove both iris cysts which were vital to achieve good result. Post-operative periods were uneventful with no significant inflammatory reactions associated with the procedure. Conclusion : Different modalities, with varying degrees of success, have been reported for the treatment of iris cysts. Surgical intervention remains the last option which can give a good functional outcome with minimal inflammatory complications, especially when less invasive options do not seem feasible due to the extensive nature of the cyst.